ANALISIS PERUBAHAN LAHAN PERUMAHAN: STUDI KASUS KORIDOR JALAN RAYA CILEDUG, TANGERANG KOTA - Dyah Nawang Ratnasari; Renny Nurhasana; Lita Sari Barus (LPPM Institut Pendidikan Nusantara Global, 2023)
The corridor of Ciledug Raya road or H.O.S. Cokroaminoto road, Ciledug, Tangerang City is developing very rapidly, especially the development of urban development and trade in the region. The development of community activities affects the use of land use functions related to social interaction spaces and community activities. This study aims to determine the occurrence of land use changes along the Ciledug Raya road, Tangerang City. The study was conducted through qualitative descriptive observation to explore information with detailed depictions so as to obtain an in-depth view of the causes of the disappearance of housing along the Ciledug highway. The results of the study show that land use is caused by an increase in activities and maximization of land to be of economic value due to open access as a place of trade. The result of this study is that changes in the use of residential land are caused by an increase in activities, additional interactions, changes in the state of buildings to changes in the use of buildings on residential land..